APANG ARUU (SEBUAH KONTRADIKTIF PEMAKNAAN IDENTITAS TELINGA PANJANG PADA MASYARAKAT SUKU DAYAK KAYAAN MENDALAAM) - Maria Nyeti Nopitasari; Imma Fretisari; Ismunandar Ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe creation of dance “Apang Aruu” was inspired from Telinga Panjang tradition in Kayaan Mendalaam, Kapus Hulu regency. This tradition as identity of Apo Kayan ethnic such as Bahau, Kenyah and Kayaan. “Apang Aruu” was symbolized as the differences of human being and monkey, statue,  gender and also the beauty symbol of dayaknesse women in Kayaan Mandalaam. As the time goes by, Telinga Panjang tradition gradually extinct because of belief, education and lifestyle in modern era. “Apang Aruu" applies method and creation stage in dance work that involves exploration, data processing, implementation, evaluation and revision. This presentation creates the aesthetics of dance performances in terms of its movement and musical accompaniment, thus it is not just a spectacle for the audiences, but it will become an artwork whose musical accompaniment is appealing and captivating to be heard by audiences. Moreover, this work combines diverse and distinctive choreography. This work is not merely entertainment work, but there is innovation in developing a regional dance and it also contains educational aspects and moral messages offered. Thus, this work is expected to be a reference or resource in the development of dance in West Kalimantan. Keywords: Apang Aruu, Telinga Panjang Tradition, Method and Creation Stage